Phosphorus Chemistry in the Earth's Upper Atmosphere. Issue 10 (12th October 2021) - Plane, John M. C.; Feng, Wuhu; Douglas, Kevin M.
Abstract: The ablation of phosphorus from interplanetary dust particles entering the Earth's atmosphere is a potentially significant source of this key bioelement. In this study, the atmospheric chemistry of phosphorus is explored by developing a reaction network of possible routes from PO, the major ablation product in the upper mesosphere/lower thermosphere region, to the stable reservoirs H3 PO3 and H3 PO4 that become incorporated into meteoric smoke particles (MSPs) as metal phosphites and phosphates, respectively. The network is constructed with reactions whose kinetics have been measured experimentally, together with reactions where theoretical rate coefficients are estimated using a combination of electronic structure theory calculations and a Rice‐Ramsperger‐Kassel‐Markus master equation treatment. The network is then incorporated into a global chemistry‐climate model, together with a phosphorus meteoric input function. The estimated global mean P deposition flux, in the form of submicron‐sized MSPs, is 1 × 10 −8  g m −2  yr −1, with a maximum of ∼5 × 10 −8  g m −2  yr −1 over the northern Rockies, Himalayas, and southern Andes. The estimated fraction of ablated phosphorus forming bioavailable metal phosphites is 11%, which results from the very large concentrations of O and H compared to OH in the upper mesosphere. A layer of OPO is predicted to occur at 90 km with a peak of concentration of ∼50 cm −3 ; this is the counterpart of the well‐known layers of meteoric metals such as Na and Fe, and may be observable spectroscopically. Key Points: A reaction network is developed in a global model for exploring the chemistry of meteor‐ablated phosphorus in the Earth's upper atmosphere A narrow layer of OPO is predicted to occur globally around 90 km, analogous to the layers of meteor‐ablated Na and Fe A significant flux of bio‐available metal phosphites is predicted to be deposited at the Earth's surface